Formulation and Evaluation of Montelukast Sodium Mucoadhesive Buccal Patches For Chronic Asthma Attacks - RAGHAVENDRA RAO N. G; SURYAKAR V. B (International Journal of Pharma and Bio Sciences, 2010)
The montelukast is a leukotrine receptor antagonist (LTRA) used for the maintenance treatment of asthma, chronic asthma attacks and to relieve symptoms of seasonal allergies. Because of poor bioavailability of montelukast sodium by oral route, there is a need to increase its bioavailability by formulating it into buccal dosage forms. Hence, montelukast sodium is a suitable drug for buccal dosage forms and may provide a better therapeutic profile than oral route. In the present research work, montelukast sodium buccal patches were prepared by using hydrophilic and hydrophobic polymers. Buccal patches were characterized for number of parameters like physical appearance and surface texture, weight uniformity, thickness, folding endurance, swelling index, surface pH, drug content uniformity, in vitro residence time, bursting strength, drug–excipients interaction study, and in vitro drug release study. All the patches were uniform and translucent, having good strength, and smooth surface. The thickness of the prepared patches was in the range of 0.266 to 0.326 mm. Folding endurance of all prepared patches was > 250. The results of swelling index between the range of 30.03 - 44.27 %, and the surface pH was in the range pH of buccal region. The results of drug content were in the prescribed range. The in vitro residence time for all the patches is in between 3.20 - 5.59 hrs. The Bursting strength of patches is in the range of 4.166 to 5.733 Kg/cm2. In vitro release studies were conducted for montelukast loaded patches exhibited drug release in the range of 68.83 - 92.22 % in 8 hrs. FT-IR studies revealed that, there was no interaction between drug and excipients used. Release of montelukast from all patches followed zero order and mechanism was diffusion rate limited. Finally it can be concluded that F3 and F6 are the best formulation.